Antibody-Drug Conjugates in Breast Cancer: Current Landscape and Future Targets (Canadian Oncology Today, 2025)
Antibody-drug conjugates (ADCs) have transformed therapeutic options for patients with breast cancer, delivering targeted cytotoxic agents with enhanced efficacy, albeit with systemic toxicity. Since the approval of trastuzumab emtansine in 2012, the ADC landscape has rapidly expanded to include agents targeting HER2, TROP-2, and other novel targets. Currently, four ADCs are approved in breast cancer, showing clinical benefit across HER2-positive, HER2-low, hormone receptor (HR)-positive and triple-negative subtypes. Trastuzumab deruxtecan has demonstrated superior outcomes compared to earlier HER2-targeted ADCs and is the preferred treatment in multiple settings. Anti-TROP-2 ADCs, such as sacituzumab govitecan and datopotamab deruxtecan, have provided improvements in progression-free survival in both triple-negative and HR-positive/HER2-negative disease. Ongoing research is exploring additional targets, such as HER3, Nectin-4, B7-H4, and CD166, with several promising candidates showing efficacy in early phase trials. As ADCs move into earlier lines of therapy and combination regimens, understanding optimal sequencing, toxicity management, and cost considerations will be essential. This review summarizes the current ADC landscape in breast cancer and highlights future directions for this rapidly evolving therapeutic class.